Du paysage au terroir viticole de forte pente : à la recherche des leviers du management territorial - Étienne Delay (Projets de Paysage)
Steep slope vineyards are perfect examples of human adaptations to environemental constraints. Through time, some of these slopes, such as the Lavaux or the Cinque Terre vineyards, have succeeded "in climbing" to a high level of recognition by being integrated into the very closed circle of Unesco World Heritage sites. Today, the slope is an important factor and determines the choice of the vine-grower in the maintenance of his plots and land transactions. We propose an ontology of the steep slope vineyard’s landscape, which we combine with field observations and a modeling approach built on Agent Based Modeling (ABM) to explore social and landscape mechanisms in action on these territories.